CAKUPAN MAKNA MAHKUM ‘ALAIH PADA MUKALLAF DAN BADAN HUKUM DALAM ANATOMI HUKUM ISLAM. - R. Fakhrurrazi; Nihayatut Tasliyah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
One of the pillars of law (arkanul hukm) in the anatomy of Islamic law is al-Mahkum alaih, namely the party who is charged with carrying out the syara' laws. Thus, those who are obliged to carry out Islamic law, carry out the law, obey the rules are mahkum alaih. Meanwhile, the scope of the meaning of mahkum alaih in classical fiqh is only focused on mukallaf. The concrete meaning of mukallaf as stated in the classical fiqh books, is a Muslim who is mature and has common sense. However, in the development of human civilization, especially in modern times, those who can take legal action and have rights and obligations, not only humans, but